2018
DOI: 10.1038/s41591-018-0087-6
|View full text |Cite|
|
Sign up to set email alerts
|

Metformin reverses established lung fibrosis in a bleomycin model

Abstract: Fibrosis is a pathological result of a dysfunctional repair response to tissue injury and occurs in a number of organs, including the lungs. Cellular metabolism regulates tissue repair and remodelling responses to injury. AMPK is a critical sensor of cellular bioenergetics and controls the switch from anabolic to catabolic metabolism. However, the role of AMPK in fibrosis is not well understood. Here, we demonstrate that in humans with idiopathic pulmonary fibrosis (IPF) and in an experimental mouse model of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
376
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(416 citation statements)
references
References 46 publications
16
376
0
Order By: Relevance
“…However, due to the lack of effective therapeutic drugs, tissue fibrosis still threatens human health. Although some drugs exhibit antifibrotic effects, including angiotensin‐converting enzyme inhibitors, aldosterone inhibitors, statins, angiotensin II type 1 receptor blockers, endothelin receptors, β‐blockers, acetylsalicylic acid, and matrix metalloproteinase (MMP) inhibitors, none of them are specifically designed to target fibrosis, and the related side effects limit their clinical use for treating fibrosis . Thus, antifibrotic and anticancer treatments are extremely urgent, and new therapeutic drugs should be designed based on specific targets that contribute to the progression of fibrosis and tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the lack of effective therapeutic drugs, tissue fibrosis still threatens human health. Although some drugs exhibit antifibrotic effects, including angiotensin‐converting enzyme inhibitors, aldosterone inhibitors, statins, angiotensin II type 1 receptor blockers, endothelin receptors, β‐blockers, acetylsalicylic acid, and matrix metalloproteinase (MMP) inhibitors, none of them are specifically designed to target fibrosis, and the related side effects limit their clinical use for treating fibrosis . Thus, antifibrotic and anticancer treatments are extremely urgent, and new therapeutic drugs should be designed based on specific targets that contribute to the progression of fibrosis and tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Although some drugs exhibit antifibrotic effects, including angiotensinconverting enzyme inhibitors, aldosterone inhibitors, statins, angiotensin II type 1 receptor blockers, endothelin receptors, β-blockers, acetylsalicylic acid, and matrix metalloproteinase (MMP) inhibitors, none of them are specifically designed to target fibrosis, and the related side effects limit their clinical use for treating fibrosis. [3][4][5][6] Thus, antifibrotic and anticancer treatments are extremely urgent, and new therapeutic drugs should be designed based on specific targets that contribute to the progression of fibrosis and tumors.Epithelial-mesenchymal transition (EMT) is a reversible terminal differentiation process in which epithelial cells shed their properties and acquire a more mesenchymal phenotype. 7 EMT is a fundamental process widely involved in the development and the progression of various diseases, and there are mainly three types of EMT 8 (Figure 1).…”
mentioning
confidence: 99%
“…12 To date, there are few studies showing promising strategies to treat pulmonary fibrosis. [3][4][5][6][7][8] Bleomycin (BLM) instillation is the most frequently used animal model of lung fibrosis in mice. 9 In this model, it has been shown that J Leukoc Biol.…”
Section: Introductionmentioning
confidence: 99%
“…First, we observed that HCPT could inhibit abnormally activated fibroblast proliferation and induced fibroblast apoptosis. Studies have shown that the TGF-β1 signaling pathway mediated fibrosis in a variety of tissues (28)(29)(30). Additionally, we reported that TGF-β1 stimulated fibroblast proliferation and tendon tissue adhesion (31,32).…”
Section: Discussionmentioning
confidence: 66%